Thyroid papillary carcinoma and hashimoto's autoimmune thyroiditis in patients operated on thyroid diseases in the precarpathian endemic goiter region. - Vovk, V. I.; Omelyash, U. V. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. A feature of thyroid pathology in the endemic goiter region is the combination in one patient of several diseases of the thyroid gland, in particular thyroid papillary carcinoma and Hashimoto’s autoimmune thyroiditis. Objective. To determine the frequency and morphological features of thyroid papillary carcinoma and Hashimoto's autoimmune thyroiditis in surgically treated patients with thyroid diseases in the Precarpathian endemic goiter region. Methods. The results of pathohistological examinations of 1348 patients operated on thyroid diseases at the Lviv Regional Clinical Hospital and the Military Medical Clinical Center of the Western Region in 2014-2018 were analyzed. Results. Among 1348 patients operated on for thyroid disease Hashimoto's autoimmune thyroiditis was found in 61 cases (4.5 %), focal thyroiditis - in 114 cases (8.5 %), thyroid papillary carcinoma - in 245 cases (18.2%), thyroid papillary carcinoma of all histological variants except papillary microcarcinoma - in 204 cases (15.1 %) and papillary microcarcinoma - in 41 cases (3.0 %). Among the total number of operated patients in 70 cases (5.2%), in each individual patient both Hashimoto's autoimmune thyroiditis or focal thyroiditis in association with thyroid papillary carcinoma were detected. Conclusion. Residents of the Precarpathian endemic goiter region operated on thyroid diseases often have cases of a combination of Hashimoto's autoimmune thyroiditis and focal thyroiditis with thyroid papillary carcinoma. These cases need further study to improve their diagnosis and treatment.